Climate Change May Increase the Drought Stress of Mesophytic Trees Downslope With Ongoing Forest Mesophication Under a History of Fire Suppression - Hwang, Taehee; Band, Lawrence E.; Miniat, Chelcy F.; Vose, James M.; Knoepp, Jennifer D.; Song, Conghe; Bolstad, Paul V. (Frontiers in Forests and Global Change, 2020)
In mountainous headwater catchments, downslope flow of subsurface water could buffer downslope forest communities from soil moisture stress during drought. Here we investigated changes in landscape-scale vegetation patterns at five forested headwater catchments in the Coweeta Hydrologic Laboratory in the southern Appalachians. We used a ca. 30-year Landsat Thematic Mapper (TM) image record of normalized difference vegetation index (NDVI), spanning a period of recorded warming since the mid-1970. We then, related spatial and temporal canopy patterns to seasonal water balance, streamflow recession behavior, and low flow dynamics from the long-term hydrologic records. All hydrologic metrics indicated increasing evapotranspiration, decreasing streamflow given precipitation, and potentially decreasing downslope subsidy at the watershed scale over time, especially during low-flow periods. Contrary to expectations, leaf area index (LAI) and basal area increased more upslope compared to downslope over time, coincident with warming. Trends in the ratio of NDVI in upslope and downslope topographic positions were also supported by long-term tree basal area increment, litterfall, and sap flux data in one of the reference watersheds. Mesophytic trees downslope appeared to respond more to frequent droughts and experience lower growth than xerophytic trees upslope, closely mediated by the isohydric/anisohydric continuum along hydrologic flow paths. Considering ongoing forest “mesophication” under a history of fire suppression across the eastern US deciduous forests, this study suggests that mesophytic trees downslope may be more vulnerable than xerophytic trees upslope under ongoing climate change due to an apparent dependence on upslope water subsidy.